Penerapan Sistem Kecerdasan Buatan pada Otomatisasi Pendeteksian Plat Nomor Ganjil Genap Kendaraan - Herdiansyah, Aditya Tri; Pratama, Arnold Agusti; Octavia, Indriyani; Baehaqi, Reza Anwar Sidiq; Saifudin, Aries; Yulianti, Yulianti (Teknik Informatika Universitas Pamulang, 2021)
The odd-even rule is a rule for categorizing odd and even vehicle number plates based on date. This rule is useful for reducing congestion on the highway. However, in applying this rule, human error still often occurs, namely the lack of accuracy of officers in supervising the number plates of passing vehicles. The more technology develops, the more applications of artificial intelligence on a device. One of them is the technology of detecting vehicle number plates automatically using the OCR (Optical Character Recognition) method. Optical character recognition is a technology that is able to convert text in an image into text that can be read by a computer. The results of the study show that this artificial intelligence system can help officers improve the accuracy of monitoring vehicle number plates.